Eradication of yaws: historical efforts and achieving WHO's 2020 target. - Kingsley Asiedu; Christopher Fitzpatrick; Jean Jannin (Public Library of Science (PLoS), 2014)
BACKGROUND:Yaws, one of the 17 neglected tropical diseases (NTDs), is targeted for eradication by 2020 in resolution WHA66.12 of the World Health Assembly (2013) and the WHO roadmap on NTDs (2012). The disease frequently affects children who live in poor socioeconomic conditions. Between 1952 and 1964, WHO and the United Nations Children's Fund (UNICEF) led a global eradication campaign using injectable benzathine penicillin. Recent developments using a single dose of oral azithromycin have renewed optimism that eradication can be achieved through a comprehensive large-scale treatment strategy. We review historical efforts to eradicate yaws and argue that this goal is now technically feasible using new tools and with the favorable environment for control of NTDs. We also summarize the work of WHO's Department of Control of Neglected Tropical Diseases in leading the renewed eradication initiative and call on the international community to support efforts to achieve the 2020 eradication goal. The critical factor remains access to azithromycin. Excluding medicines, the financial cost of yaws eradication could be as little as US$ 100 million. CONCLUSIONS:The development of new tools has renewed interest in eradication of yaws; with modest support, the WHO eradication target of 2020 can be achieved.